Ответ:
Объяснение:
а) [tex]\sqrt{x^{2}-3x}=2x-2[/tex]
[tex]x^{2}-3x=(2x-2)^{2}[/tex]
[tex]x^{2}-3x=4x^{2}-8x+4[/tex]
[tex]-3x^{2}+5x-4=0[/tex]
[tex]D=5^{2}-4*(-3)*(-4)=25-48=-23 < 0[/tex] - корней нет
Ответ: корней нет.
б) [tex]\sqrt{2x+1}-\sqrt{x} =1[/tex]
[tex]2x+1-2\sqrt{x}\sqrt{2x+1}+x=1[/tex]
[tex]-2\sqrt{x(2x+1)}=-3x[/tex]
[tex]4*(2x^{2}+x)=(-3x)^{2}[/tex]
[tex]8x^{2}+4x=9x^{2}[/tex]
[tex]-x^{2}+4x=0[/tex]
[tex]x(-x+4)=0[/tex]
[tex]x=0[/tex] или [tex]-x+4=0[/tex]
[tex]-x=-4[/tex]
[tex]x=4[/tex]
Ответ: [tex]x=0[/tex], [tex]x=4[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
а) [tex]\sqrt{x^{2}-3x}=2x-2[/tex]
[tex]x^{2}-3x=(2x-2)^{2}[/tex]
[tex]x^{2}-3x=4x^{2}-8x+4[/tex]
[tex]-3x^{2}+5x-4=0[/tex]
[tex]D=5^{2}-4*(-3)*(-4)=25-48=-23 < 0[/tex] - корней нет
Ответ: корней нет.
б) [tex]\sqrt{2x+1}-\sqrt{x} =1[/tex]
[tex]2x+1-2\sqrt{x}\sqrt{2x+1}+x=1[/tex]
[tex]-2\sqrt{x(2x+1)}=-3x[/tex]
[tex]4*(2x^{2}+x)=(-3x)^{2}[/tex]
[tex]8x^{2}+4x=9x^{2}[/tex]
[tex]-x^{2}+4x=0[/tex]
[tex]x(-x+4)=0[/tex]
[tex]x=0[/tex] или [tex]-x+4=0[/tex]
[tex]-x=-4[/tex]
[tex]x=4[/tex]
Ответ: [tex]x=0[/tex], [tex]x=4[/tex]